Pest D Attack Tef! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Mulegata Seyoum, Gondar, Ethiopia: 'I would like to comment on Dr Tsedeke Abate's statement at the CTA seminar abouttef pest attack as indicated on page 4 of May-June Spore edition. Tef is attacked and highly infested by grasshoppers, red...